Different Clinical Features of Acral Abortive Hemangiomas - N. Vega Mata; J. C. López Gutiérrez; B. Vivanco Allende; M. S. Fernández García (Case Reports in Dermatological Medicine)
Some infantile hemangiomas called in literature “minimal or arrested growth hemangiomas” or “abortive hemangiomas” are present at birth and have a proliferative component equaling less than 25% of its total surface area. Often, they are mistaken for vascular malformation. We present five patients (three girls and two boys) with abortive hemangiomas diagnosed between January 2010 and December 2015 localized in acral part of the extremities. They were congenital lesions resembling precursor of hemangiomas but did not show proliferation phase. Immunohistochemical Glut-1 was performed in all of them as a way to confirm the abortive hemangioma diagnosis. The most common appearance was a reticulated erythematous patch with multiple fine telangiectasias on the surface. We remark that one of them presented a segmental patch with two different morphologies and evolutions. The proximal part showed pebbled patches of bright-red hemangioma and presented proliferation and the distal part with a reticulated network-like telangiectasia morphology remained unchanged. We detected lower half of the body preference and dorsal region involvement preference without ventral involvement. The ulceration occurred in three patients with two different degrees of severity.